81.6k views
24 votes
What is the solution to the equation 6- t = 2t

2 Answers

12 votes

Answer:

t=2

Explanation:

Literally just move all the common like terms onto one side.

6=3t

It is usually prefered to have the variables on the left and the coefficients on the right so you would flip your equation.

3t=6

Then you get t by itself by dividing by 3. Your final answer should be 2.

User Morgant
by
5.1k points
10 votes
-t + 6= 2t hope it help
User Shardae
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.